Pemanfaatan Produk Pertanian yang Biodegradable pada Home Industry Pengolahan Aloe vera menjadi Nata de Aloevera - Maria Atik Sunarti Ekowati Subroto; Kristyana Dananti; Sri Wening (CV. ALIM'SPUBLISHING, 2023)
This Community Service activity aims to optimize the use of environmentally friendly agricultural products in the home industry for processing aloe vera into nata de aloevera. The agricultural products used are rice straw waste and bagasse which are processed into biodegradable raw materials. The experiment was carried out using a completely randomized design (CRD) with three treatments namely A (50% waste rice straw + 50% bagasse), B (75% waste rice straw + 25% bagasse), and C (25% waste rice straw + 75% bagasse). Measurements were made of the parameters pH, total acid, water content, protein content, and organoleptic nata de aloevera. The results showed that treatment A gave the best results in terms of pH, total acid, and protein content. Meanwhile, C treatment gave the best results on water content and organoleptic. It is hoped that the results of this research can provide alternatives to the use of environmentally friendly raw materials in the home industry for processing aloe vera into nata de aloevera and can meet consumer needs for healthy and safe food products.. Keywords: Biodegradable agricultural products, Home industry, Aloe vera processing, Nata de aloevera, Green technology, Green technology Abstrak_Indo. Kegiatan Pengabdian pada Masyarakat ini bertujuan untuk mengoptimalkan pemanfaatan produk pertanian yang ramah lingkungan pada home industry pengolahan aloe vera menjadi nata de aloevera. Produk pertanian yang digunakan adalah limbah jerami padi dan ampas tebu yang diolah menjadi bahan baku biodegradable. Percobaan dilakukan dengan menggunakan rancangan acak lengkap (RAL) dengan tiga perlakuan yaitu A (50% limbah jerami padi + 50% ampas tebu), B (75% limbah jerami padi + 25% ampas tebu), dan C (25% limbah jerami padi + 75% ampas tebu). Pengukuran dilakukan terhadap parameter pH, total asam, kadar air, kadar protein, dan organoleptik nata de aloevera. Hasil penelitian menunjukkan bahwa perlakuan A memberikan hasil terbaik pada parameter pH, total asam, dan kadar protein. Sementara itu, perlakuan C memberikan hasil terbaik pada kadar air dan organoleptik. Diharapkan hasil dari penelitian ini dapat memberikan alternatif pemanfaatan bahan baku yang ramah lingkungan dalam home industry pengolahan aloe vera menjadi nata de aloevera serta dapat memenuhi kebutuhan konsumen pada produk makanan yang sehat dan aman. Kata kunci: Produk pertanian biodegradable, Industri rumahan, Pengolahan lidah buaya, Nata de aloevera, Teknologi hijau, Teknologi hijau.